Eye of the storm : chasing storms with Warren Faidley - Kramer, Stephen P. (G.P. Putnam's Sons, 1997)
Storm chaser Warren Faidley discusses the techniques, dangers, and difficulties of photographing lightning, tornadoes and hurricanes.